Code Alternations in Bilingual Representation and a Communication Strategy in Tuan Guru Bajang’s Islamic Speech - Lalu Thohir (Universitas Islam Negeri Walisongo Semarang, 2017)
The present writing is a study of code alternation in TGB’s Islamic speech. TGB which stands for “Tuan Guru Bajang” is a well-known name for Dr. M. Zainul Majdi, M.A, a famous Islamic preacher in Lombok and at present, he is the governor of West Nusa Tenggara province. The data of this study were obtained from one of TGB’s Islamic speech recordings. They were first classified into inter-sentential switching, tag-switching, and intra-sentential switching and then they were analyzed to know their functions which involve a topic switch, effective and repetitive functions. The findings show that intra-sentential switching which reflects repetitive function appeared most frequently in TGB’s Islamic speech. The code alternation in TGB’s Islamic speech represents bilingualism and has proved to be an effective strategy in communication.